MENGKAJI PENGARUH KURIKULUM MERDEKA TERHADAP PEMBENTUKAN BUDAYA SEKOLAH YANG POSITIF: STUDI LITERATUR - A.N. Sulaeman; Dian Dinarni; Aep Saepuloh; Lela Nurlaila; Rosyida Nurul Anwar (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
This study aims to examine the impact of the Merdeka Curriculum on the formation of a positive school culture. The primary focus is to understand how the implementation of this curriculum can affect various aspects of school culture, such as social climate, adopted values, and the patterns of interaction among students, teachers, and school staff. This research employs a literature review method, which involves reviewing and analyzing relevant written sources related to the research topic. The literature review identifies key sources by gathering journal articles, books, reports, and other documents pertinent to the research topic. The findings indicate that the Merdeka Curriculum in Indonesia, designed to replace the previous rigid curriculum, aims to provide greater flexibility for schools and teachers in a student-centered learning process. Supported by the government and educational institutions through training and resources, this curriculum seeks to create a more adaptive and responsive learning environment. This approach not only enhances student engagement and motivation through techniques such as project-based learning and collaboration but also encourages teachers to develop innovative teaching methods. Additionally, the emphasis on character values and life skills within the Merdeka Curriculum contributes to the development of a more positive and inclusive school culture and improves social relationships within the school environment. Thus, the Merdeka Curriculum is expected to support students' personal and academic development and foster a more harmonious and effective school climate.